Color preferences for cartographic symbol designs of urban buildings in western São Paulo State on topographic maps at a 1:10,000 scale - Grassi, Gustavo [UNESP]; Pugliesi, Edmur Azevedo [UNESP] (FapUNIFESP (SciELO), 2024)
This research aims to evaluate the preference for cartographic symbol designs that depict urban buildings for topographic maps at a 1:10,000 scale, to define symbols that may represent part of the western urban landscape of the state of São Paulo. Three proposals were designed to represent buildings: Pink visually coherent with the national cartographic standards; Orange visually coherent with the urban landscape of the western portion of São Paulo state; Gray visually coherent with the digital navigational maps used frequently. Map evaluation considered the preference for the symbol designs between architects and non-architects. The Orange design was the most preferred in all aspects. Despite that, Orange and Pink designs did not present statistically significant differences, but Gray was the least preferred. Furthermore, from the statistical analysis, map users with a background in architecture and those with other backgrounds could be considered as part of the same population.
Keywords: Landscape; Map Preference; Symbol Design; Topographic Map